Reliability of task graph schedules with transient and fail-stop failures: complexity and algorithms - Benoit, Anne; Canon, Louis-Claude; Jeannot, Emmanuel; Robert, Yves (Journal of scheduling, 2012)
This paper deals with the reliability of task graph schedules with transient and fail-stop failures. While computing the reliability of a given schedule is easy in the absence of task replication, the problem becomes much more difficult when task replication is used. We fill a complexity gap of the scheduling literature: our main result is that this reliability problem is # P ′-Complete (hence at least as hard as NP-Complete problems), both for transient and for fail-stop processor failures. We also study the evaluation of a restricted class of schedules, where a task cannot be scheduled before all replicas of all its predecessors have completed their execution. Although the complexity in this case with fail-stop failures remains open, we provide an algorithm to estimate the reliability while limiting evaluation costs, and we validate this approach through simulations.